Efforts on reducing dietary salt intake and its associated factors among medical students in Universiti Putra Malaysia - Lee, Zhan Yue; Zainudin, Nur Shafeeqah; Ahmad Pauzi, Afifah Alya; Rashid, Aneesa Abdul; Cheong, Ai Theng (Universiti Putra Malaysia, 2021)
Introduction: Increased dietary salt intake can cause retention of fluid and subsequently an increase in blood pressure. Excessive salt consumption is one of the main causes of hypertension. This study aims to determine efforts done by medical students to reduce dietary salt intake and its associated factors in Universiti Putra Malaysia (UPM). Methods: This is a cross-sectional study. A self-administered questionnaire looking into efforts to reduce dietary salt intake adapted from the WHO STEPS questionnaire was used. There were six efforts altogether which were; limiting consumption of processed food; looking into sodium contents on food labels; purchasing low salt or sodium alternatives; avoid eating out; using spices when cooking; and doing things specifically to control salt consumption. Other factors in this questionnaire are on socio-demographic, practice of salt consumption, awareness, perception, attitude of dietary salt intake. Results: A total of 362 respondents participated. The majority had good awareness on salt intake (98.1%). A larger proportion of females significantly made the effort to buy low salt alternatives (p=0.003) and avoided eating out (p=0.048). On salt consumption practice, there were a bigger proportion of those that rarely ate processed food, that avoided eating out (p=0.08), bought low salt/sodium alternatives (p<0.001), looked at the sodium contents on labels (p=0.027) and limited the consumption of processed food (p<0.001). Conclusion: There are significant associations between the female gender and practice of eating processed food with efforts to decrease salt intake. More studies are recommended to look into assisting efforts to reduce salt consumption.